Subcontractors Selection of Building Construction Project Using Analytical Hierarchy Process (AHP) and Technique for Others Reference by Similarity (TOPSIS) Methods - Caesarani Gloria Putri; Dewi Nusraningrum (Jurnal Manajemen Teori dan Terapan, 2022)
Objective: This research aims to identify the most important qualification criteria for selecting subcontractors in the construction supply chain.